Effect of segregated Al on { 1012 } and { 1011 } twinning in Mg. Issue 23 (3rd November 2015) - Miyazawa, Naoki; Yoshida, Takashi; Yuasa, Motohiro; Chino, Yasumasa; Mabuchi, Mamoru
Abstract: Abstract : Molecular dynamics simulations of compression deformation of [ 1120 ] -textured 2-dimensional polycrystalline pure Mg, Mg–0.1 at.%Al, and Mg–1.0 at.%Al models were performed at 5 and 300 K. A { 1011 } twin nucleated before formation of a { 1012 } twin in the simulations at 5 K, while a { 1011 } twin nucleated after formation of a { 1012 } twin in the simulations at 300 K. The formation of a { 1011 } twin was the result of the glide of pyramidal 〈 c + a 〉 partial dislocations of 1 / 1 6 . - ulldelimiterspace 6{ 1011 }[ 2023 ] . { 1011 } twin formation was suppressed at the sites around the Al atoms because the strong Mg–Al bond suppresses atomic shuffling. However, formation was not suppressed at the sites away from the Al atoms because the effect of strong Mg–Al bond is short range. On the other hand, because { 1012 } twinning requires the simultaneous glide of zonal dislocations, Al inevitably suppressed { 1012 } twinning.